2003
DOI: 10.1002/jms.456
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometry of the B‐type procyanidins in wine and B‐type dehydrodicatechins in an autoxidation mixture of (+)‐catechin and (−)‐epicatechin

Abstract: We describe the characterization of the B-type procyanidins in wine and the B-type dehydrodicatechins (dimeric flavan-3-ols) obtained for the autoxidation of (+)-catechin and (-)-epicatechin by tandem mass spectrometry (MS/MS) coupled to reversed-phase high-performance liquid chromatography (HPLC). The MS/MS analysis demonstrates that the interesting major fragments derive from the dissociations of the C-ring on the catechin or epicatechin unit, such as retro-Diels-Alder reactions. The two kinds of dimers give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 19 publications
6
76
0
Order By: Relevance
“…Other polyphenol derivatives have been recently described. Dehydrodimers of flavan-3-ols can be formed from the oxidation of (+)-catechin and (−)-epicatechin (Sun & Miller, 2003). Correlation data obtained confirm that the new compounds named together as "undetected" derivatives formed during the process of intestinal digestion may contribute to the antioxidant activity of the sample digested.…”
Section: Correlation Between Antioxidant Activity and Chemical Composmentioning
confidence: 64%
See 1 more Smart Citation
“…Other polyphenol derivatives have been recently described. Dehydrodimers of flavan-3-ols can be formed from the oxidation of (+)-catechin and (−)-epicatechin (Sun & Miller, 2003). Correlation data obtained confirm that the new compounds named together as "undetected" derivatives formed during the process of intestinal digestion may contribute to the antioxidant activity of the sample digested.…”
Section: Correlation Between Antioxidant Activity and Chemical Composmentioning
confidence: 64%
“…In mass spectra, two groups of different masses corresponding to monomers and dimers of flavan-3-ol were detected ( Table 2). Much of the literature on flavan-ols by LC-MS has used negative electrospray (ESI) as the ionisation mode of choice as it has been reported to give improved sensitivity (Sun & Miller, 2003). However, more recently both negative and positive ESI have been utilised as the two dataset can often provide complementary information (Li & Deinzer, 2008).…”
Section: Identification Of Individual Compounds By Hplc-dad and Hplc-mentioning
confidence: 99%
“…Some polyphenol derivatives have been described in other studies. Previous studies have found that dehydrodimers of flavan-3-ols can be formed from the oxidation of (+)-catechin and (−)-epicatechin (Sun & Miller, 2003). Some putative dimmers and phenolic compounds can be derived from anthocyanidins (Aura et al, 2005;Fleschhut, Kratzer, Rechkemmer, & Kulling, 2006), and protocatechuic acid can be formed by spontaneous degradation from cyanidin (Fleschhut et al, 2006).…”
Section: Total Phenolic Content Of 23 Edible Flowersmentioning
confidence: 99%
“…For comparison purposes, a commercial grape seed extract has been analysed under the same conditions, as the PA composition of such extracts has been extensively examined by LC-MS (Gabetta et al, 2000;Monagas et al, 2006;Weber et al, 2006). Much of the literature on polyphenolics by LC-MS has utilised negative electrospray (ESI) as the ionisation mode of choice as it has been reported to give improved sensitivity (Sun and Miller, 2003). However, more Fig.…”
Section: Detection and Validation Of Pas In Teamentioning
confidence: 99%